Development Of Student Worksheet Oriented On Steam With PjBL Model On Environmental Pollution Matter To Improve Creative Thinking Skill - Desta Alvionita Desta (JPMP, 2021)
This study aims to determine the feasibility of student's worksheet oriented STEAM with PjBL model on environmental pollution material to improve creative thinking skills based on validity, practicality, and effectiveness. This research method uses a 4-D model which is limited only to the development stage because at the dissemination stage a larger population is required, and a limited trials are carried out to eighteen students of MTsN 3 Jombang. The results of the research on the aspect of validity based on content and construct validity show the percentage score of 89.17% and 95.02% on very valid category. The practicality aspect in terms of activity observation and student response for each component obtained a percentage score of 98.53% and 97.02% on very practical category. The aspect of effectiveness in terms of the results pretest-posttest of students' creative thinking skills showed an increase in the average N-Gain score of 0.72 on very high category and declared effective.